2022
DOI: 10.1017/njg.2022.8
|View full text |Cite
|
Sign up to set email alerts
|

Implications of the statistics of seismicity recorded within the Groningen gas field

Abstract: We reanalysed the induced seismicity data from the Groningen gas reservoir. We used the well-maintained induced event catalogue of the KNMI. The distributions of seismic moments and interevent times show a power law behaviour over several decades, and we find that upon increasing the magnitude threshold, these distributions remained scale-invariant. Because of this scale-invariance, we can put a constraint on the average loading of the elastic energy within the reservoir, which upon reaching a critical value g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…They employed the random forest model to classify activities overlapping in the spatiotemporal distance space. Trampert et al (2022) assumed the interevent-time distribution of induced earthquakes around gas reservoirs as a mixture of Omori, gamma, and exponential distributions. By applying gradient boosting regression, they concluded that the proportion of the Omori distribution (i.e., the fraction triggered by other earthquakes) was small.…”
Section: Other Applications In Seismicity Analysismentioning
confidence: 99%
“…They employed the random forest model to classify activities overlapping in the spatiotemporal distance space. Trampert et al (2022) assumed the interevent-time distribution of induced earthquakes around gas reservoirs as a mixture of Omori, gamma, and exponential distributions. By applying gradient boosting regression, they concluded that the proportion of the Omori distribution (i.e., the fraction triggered by other earthquakes) was small.…”
Section: Other Applications In Seismicity Analysismentioning
confidence: 99%
“…The Groningen region in the Netherlands has been studied extensively in the context of induced seismicity (e.g., Nepveu et al, 2016;Hettema et al, 2017;Bourne et al, 2018;Trampert et al, 2022) and subsidence (e.g., Van Thienen-Visser et al, 2015;Van der Wal & Van Eijs, 2016;Van Thienen-Visser & Fokker, 2017). The installation of a large dense network of borehole geophones (Dost et al, 2017) enabled intensive research activity.…”
Section: Groningen Setting Data and Modelsmentioning
confidence: 99%
“…The Groningen region in the Netherlands has been studied extensively in the context of induced seismicity (e.g., Bourne et al., 2018; Hettema et al., 2017; Nepveu et al., 2016; Trampert et al., 2022) and subsidence (e.g., Van der Wal & Van Eijs, 2016; Van Thienen‐Visser & Fokker, 2017; Van Thienen‐Visser et al., 2015). The installation of a large dense network of borehole geophones (Dost et al., 2017) enabled intensive research activity.…”
Section: Groningen Setting Data and Modelsmentioning
confidence: 99%